2020
DOI: 10.1016/j.heliyon.2020.e03554
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Arabic sign language dynamic gesture recognition models

Abstract: Arabic Sign Language (ArSL) is similar to other sign languages in terms of the way it is gestured and interpreted and used as a medium of communication among the hearing-impaired and the communities in which they live in. Research investigating sensor utilization and natural user interfaces to facilitate ArSL recognition and interpretation, is lacking.Previous research has demonstrated that there is not a single classifier modeling approach that can be suitable for all hand gesture recognition tasks, therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The system performance was tested, which indicated that the highest accuracy rate was 99 %. Almasre and Al-Nuaim [17] proposed a Kinect-based prototype model for recognition of specific Arabic Sign Language hand gesture words. This model obtained 83 % offline classification accuracy using SVM, RF and KNN algorithms.…”
Section: Related Studiesmentioning
confidence: 99%
“…The system performance was tested, which indicated that the highest accuracy rate was 99 %. Almasre and Al-Nuaim [17] proposed a Kinect-based prototype model for recognition of specific Arabic Sign Language hand gesture words. This model obtained 83 % offline classification accuracy using SVM, RF and KNN algorithms.…”
Section: Related Studiesmentioning
confidence: 99%
“…Almasre et al [17] proposed a dynamic prototype model (DPM) that recognizes some ARSL gestured dynamic words using Kinect as a sensor. The DPM used eleven predictive models based on three algorithms' various parameter settings (SVM, RF, and KNN).…”
Section: Related Workmentioning
confidence: 99%
“…Arabic is the 4th most spoken language in the world. Arabic Sign Language (ArSL) was a certified main language for talking and listening impaired in Arab nations [1]. Although Arabic is one of the global key languages, ArSL was still in its initial levels [2].…”
Section: Introductionmentioning
confidence: 99%